CREATIVE WRITING LEARNING IN NATURE SCHOOL2017 - Vedia, Vedia; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2017)
This study was aimed to get a picture of creative writing learning in the 4th grade of Sekolah AlamTangerang. This research used an ethnography method. The data were collected through observation, documentation, and interview. The research showed that: (1) The type of syllabus used was a syllabus referring to the SAT curriculum and national curriculum. (2) The formulation of learning objectives was the maturity in creative writing. (3) The materials developed by the teachers included learning to write journal or book report, poem, comic, and article. (4) The strategies, approaches, methods, and techniques used refer to experience from the natural environment. (5) The roles of teachers and students in learning were equally important. (6) The most important infrastructures and learning media were nature-based. (7) The evaluation system used was more concerned with daily assessment. Overall, the creative learning process at the 4th grade of Sekolah Alam Tangerang forms its own cultural theme; that is nature-based learning.